Radar measurements on drones, birds and humans with a 77GHz FMCW sensor. - Alexander Karlsson (Royal Institute of Technology, 2021)
This data set contains radar measurements on birds, humans and six different drones with a total of 75868 samples.

The sensor was a  frequency modulated continuous wave (FMCW) radar operating at 77 GHz with a mechanically scanning antenna.

The 'ReadMe.txt' file contains a detailed description of the data.

The data set is used in [1] where only FM-sweeps corresponding to azimuth index 54 to 203 are used (out of the provided 256), or 150 sweeps.

When using this data set please refer to:

[1] A. Karlsson, M. Jansson and M. Hämäläinen, "Model-Aided Drone Classification Using Convolutional Neural Networks," 2022 IEEE Radar Conference (RadarConf22), 2022, pp. 1-6, doi: 10.1109/RadarConf2248738.2022.9764194.

The data in version 1.0 and 2.0 is identical apart from the format, ".mat" in 1.0 and ".npy" in 2.0
Keywords: FMCW radar, drone, bird; Electrical Engineering, Electronic Engineering, Information Engineering; Elektroteknik och elektronik